Transactions on Computational Collective Intelligence XIX - Nguyen, Ngoc Thanh; Kowalczyk, Ryszard; Xhafa, Fatos; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
These transactions publish research in computer-based methods of computational collective intelligence (CCI) and their applications in a wide range of fields such as the semantic Web, social networks, and multi-agent systems. TCCI strives to cover new methodological, theoretical and practical aspects of CCI understood as the form of intelligence that emerges from the collaboration and competition of many individuals (artificial and/or natural). The application of multiple computational intelligence technologies, such as fuzzy systems, evolutionary computation, neural systems, consensus theory, etc., aims to support human and other collective intelligence and to create new forms of CCI in natural and/or artificial systems. This nineteenth issue contains 11 carefully selected and revised contributions.
Management and Computer Science Synergies: a theoretical framework for context sensitive simulation environment -- Improved Recommendation System Using Friend Relationship in SNS -- Bidirectional Analysis Method of Static XSS Defect Detection Technique Based on Database Query Language -- A Multilevel Security Model for Search Engine over Integrated Data -- Security Analysis of Two Identity Based Proxy Re-encryption Schemes in Multi-user Networks -- Enabling Vehicular Data with Distributed Machine Learning -- Enabling Vehicular Data with Distributed Machine Learning -- Adapting Distributed Evolutionary Algorithms to Heterogeneous Hardware -- Eroca: A Framework for Efficiently Recovering Outsourced Ciphertexts for Autonomous Vehicles -- Coarser-Grained Multi-user Searchable Encryption in Hybrid Cloud -- Quantum information splitting based on entangled states -- Zero-tree Wavelet Algorithm joint with Huffman Encoding for Image Compression.
Keywords: Artificial intelligence; Engineering; Software engineering; Computer science; Computer simulation; Information systems; Artificial Intelligence; Computational Intelligence; Software Engineering; Computation by Abstract Devices; Simulation and Modeling; Information Systems and Communication Service